The 9th ambassadorial lecture series by His Excellency Jose Luis Pardo Cuerdo Ambassador of Spain to Malaysia / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
On behalf of the Vice-Chancellor of UiTM, Professor Datuk Ts. Dr Hajah Roziah Mohd Janor, I am pleased to welcome everyone to the 9th Ambassadorial Lecture Series. Professor Datuk sends her warmest regards to everyone, especially to our distinguished guest, His Excellency Jose Luis Pardo Cuerdo, Ambassador of Spain to Malaysia who will speak on "Malaysia and Spain: Crossed Realities."